An optimal blend of single auto displayed cellulases for cellulose saccharification – a proof of concept - Eugene Marfo Obeng; Clarence M. Ongkudon; Cahyo Budiman; Ruth Maas; Joachim Jose (2018)
BACKGOUND: To date, it has been challenging to determine the optimal proportions of the individual cellulases in crude extracts and multienzyme systems to promote enzyme synergism. The application of single surface-display of enzymes may obviate such challenges. This article presents a proof of concept of the optimal mixing of single surface-displayed cellulases for cellulose hydrolysis using Simplex lattice mixture design. RESULTS: The recently discovered maximized autotransporter-mediated expression system was used to express the three cellulases. The biochemical screening analysis revealed that the enzymes have a broad range of functional pH (4–9) and temperature (30–100 ∘C) characteristics. The evaluated optima were pH 6 and 60 ∘C. Through the statistical design of experiment, a blend ratio of 1: 1.6: 1.4 of endoglucanase: exoglucanase: